Preparation, identification, computational analysis of antioxidative peptides derived from Lumbricus protein and prevention of UV-B radiation-induced skin damaged. (April 2023) - Zhao, Mengge; Li, Boyuan; He, Hui; Hou, Tao
Abstract: Present study aimed to prepare, identify and computational analysis antioxidative peptides from Lumbricus protein, meanwhile to investigate their bioavailability and preventive effects against oxidative stress-related diseases, namely UV-B radiation-induced skin damaged. Antioxidative peptides from Lumbricus protein (Mw < 5 kDa, LPs) hydrolyzed by alcalase reached the highest ABTS· + scavenging activity and Fe 2+ chelating activity with the EC50 values of 0.175 and 1.003 mg/mL, respectively. Additionally, UV-B radiation-induced skin damaged mice model showed that skin catalase (CAT) and glutathione (GSH) were enhanced, while malondialdehyde (MDA) was decreased by LPs significantly ( p  < 0.05). LPs could inhibit skin oxidative stress via regulating the expression and distribution of B-cell lymphoma 2 (Bcl-2) and Bcl-2 associated X (Bax). Moreover, eighty peptides were identified in LPs, peptides such as PGAGAVY and KDLY showed the lowest binding energies with ABTS, and their binding affinities were confirmed by molecular docking. At the concentration of 0.0625 mg/mL, the ABTS· + scavenging activity of PGAGAVY and KDLY reached 63.016%, and 52.884%, respectively, which were better than that of LPs (EC50  = 0.175 mg/mL). Overall, these findings provide a new perspective for Lumbricus antioxidative peptides as natural antioxidants. Graphical abstract: Lumbricus peptides are highlighted to exert antioxidant activity through the UV-B radiation-induced skin damaged mouse model. Two new peptides (PGAGAVY and KDLY) were identified and molecular docking with ABTS·. Image 1 Highlights: LPs prepared by Alcalase hydrolysis showed high antioxidant ability. LPs could regulate the Bcl-2 and Bax level in UV-B-induced oxidant stress. 80 peptides sequences were characterized by HPLC-ESI-MS/MS. The interaction between LPs and ABTS. was determined by molecular docking. PGAGAVY and KDLY showed better antioxidant effects than that of the LPs.